Частота діабетичної полінейропатії серед дітей із цукровим діабетом 1-го типу - Абедимова, Р. (Clinical Endocrinology and Endocrine Surgery, 2012)
205 children with diabetes mellitus type one from Almaty city were investigated at the age of 3 till 16 years. The duration of the diabetes mellitus was from 6 months to 10 years (2.73±2.58). The diabetic neuropathy was found in 72.68% of cases, and in 55.03% of them had subclinical disease manifestations.